Interleukin‐10 levels increase in cutaneous biopsies of patients undergoing wasp venom immunotherapy - Nasser, S. M. Shuaib; Ying, Sun; Meng, Qiu; Kay, A. Barry; Ewan, Pamela W. (European journal of immunology, 2001)
We have studied the influence of wasp venom immunotherapy (VIT) on cellular recruitment and cytokine mRNA expression during allergen‐induced cutaneous late‐phase responses (LPR). Nine subjectswith a history of wasp sting anaphylaxis, and specific IgE in their sera underwent wasp VIT. Skin biopsies were taken 24 h after intradermal diluent and allergen before and after 3 months VIT. Pre‐immunotherapy, there were significant allergen‐induced increases in EG2+ eosinophils, elastase+ neutrophils, CD68+ macrophages and IL–10 protein+ cells, and increased expression of mRNA for IL–4, IL–13, IFN–γ, IL–12, IL–10, TGF‐β, RANTES and eotaxin. When these allergen‐induced changes in cytokine mRNA and cellular profiles were compared with those obtained after 3 months VIT there was a significant reduction in IL–4 mRNA (p=0.012) and increase in IL–10 protein+ cells (p=0.004) with a trend to an increase in IL–10 mRNA (p=0.054). There were also significant reductions in eosinophils (p<0.004) and the size of the cutaneous LPR (p<0.01) but no change in mRNA to IFN–γ, IL–13 or IL–12. Therefore, VIT is associated with a significant increase in cells positive for IL–10 protein but not IL–12 or IFN–γ. These results suggest that induction of IL–10 may be important in VIT and occur independently of the switch to a Th1 phenotype. IL–10 generation may down‐regulate IL–4 expression and eosinophil recruitment.